Human resource management BMS 3rd year 5th semester - Kale N.G. amd Ahmed Mehtab (Vipul prakashan, Mumbai, 2005)
B.M.S.
ENGLISH
Keywords: Human resource management BMS 3rd year 5th semester; B.M.S.; B.M.S.